Evaluation of Corrosivity and Scaling Potential of Groundwater using Saturation Indices in Idri Municipality, Wadi Al Shatti - Omar, Om Alsaad; Binyehmed, Fadel; Alshareef, Ibraheem (Journal of Pure & Applied Sciences, 2023)
Corrosivity and scaling tendency of water is an etiology of economic and health concerns in the water supply systems. The corrosivity of water and its ability to form calcium carbonate scales are economic and health concerns in water supply systems. The aim of this study is to verify the stability of water in the distribution systems of drinking water and irrigation water in some groundwater wells in Idri municipality, Wadi Al Shati. Physiochemical tests were conducted for 12 well samples in the study area, including water temperature, pH, total dissolved salts (TDS), calcium hardness and total alkalinity. Water stability was determined using the Langelier Saturation Index (LSI) and the Ryznar Stability Index (RSI). The results of the physicochemical analysis showed that the mean of pH, temperature, TDS, calcium hardness, and total alkalinity were 7.05±0.39, 19.87±4.11 C0, 832.64±104.34 mg/L, 62.58±49.79 mg/L, and 11.03±2.20 mg/L, respectively. The results also showed that the majority of the samples are highly corrosive, as the LSI index ranged between -0.87 to -2.9, where the Mansoura M2 well was less corrosive, and the Al-Hatiya H2 well was the highest corrosive according to the LSI index. In addition, the findings showcased that the RSI values ranged between 9.7 to 12, in general, these values are considered high based on RSI index, which means that this water is very aggressive. Furthermore, the wells that showed high corrosivity were soft water with a low calcium level, which means that they are unable to form scales which protect metals’ surface from corrosion attack. On the other hand, the results exhibited that wells such as T3 (medium hardness), M1 (very hard) and M2 (medium hardness) were less corrosive according to Langelier, and therefore the corrosivity would be lower due to their simple ability to form scales.